CANONICAL ROOT ANALYSIS AND CLUSTERING FOR CHARACTERIZATION AND EVALUATION OF AROMATIC RICE GERMPLASM BASED ON MORPHOLOGICAL CHARACTERS - G. PARIMALA; CH. DAMODHAR RAJU; L.V. SUBBA RAO; K. UMA MAHESWARI (The Bioscan, 2020)
The present study was conducted to estimate the magnitude of genetic diversity among the genotypes and to identify the major morphological traits contributing for the observed variations. A total of 50 aromatic rice genotypes were evaluated in Randomized Block Design with three replications during -2018-2019 kharif season to study genetic diversity using Mahalanobis D² statistics for seed yield and its components. Cluster analysis classified the fifty genotypes into 12 groups. Maximum inter cluster distance was exhibited between clusters VIII and IX (227.03) followed by clusters I and IX (199.86), clusters VII and VIII (190.65), clusters V and IX (187.34) and cluster VII and IX (180.52). The lowest inter cluster divergence was observed between clusters IV and VII (11.01). The intra-cluster distance (D) ranged from 10.23 (cluster-I) to 25.36 (cluster-XII). The attributes, viz., 1000 grain weight (37.63%), Plant height (25.71%) and Seed yield per plant (18.61%) contributed much to the total genetic divergence. PCA revealed three most informative principal components with Eigen values of 6.222, 4.577 and 1.900, respectively, which together accounted 83.323 % of the total variance. The result ensures the existence of high genetic divergence among the studied genotypes and can be used by breeders to develop high yielding rice varieties and have immense applications in rice improvement.